Growth pattern of three species of Mullets (Pisces: Mugilidae) in Sombreior River, Rivers State, Niger Delta, Nigeria - Henry Eyina Dienye; Olaniyi Alaba Olopade (Aceh Journal of Animal Science, 2020)
Length-weight relationships (LWRs) and condition factor are important biological information to assess the growth pattern and wellbeing of fish species influenced by numerous abiotic and biotic factors. To date, no data on the LWRs and condition of mullets in Sombreior River, Niger Delta. Hence, this research was conducted to determine abundance, length–weight relationship and Fulton’s condition factor (K) of three species of fish belonging to family Mugilidae in Sombreior River, Nigeria. There were a total of 248 samples from five sampling stations for a period of months. Fish species were of various sizes ranging from 24.66±0.40 to 26.35±0.26cm in length and 141.41±6.30 to 161.56±5.87g in weight. For the three species, slope (b) values ranged from 2.18 to 2.68 indicating a negative allometric growth of all fish species. The mean condition factor ranged from 0.89±0.03 forsix Mugil cephalus to 0.93±0.03 for Parachelon grandisquamis while the coefficients of determination (R2) of the LWR regressions ranged between 0.64 (Neochelon falcipinnis) and 0.79 (Parachelon grandisquamis). It was concluded that the mullets in the Sombreior River had a negative allometric growth pattern and the condition is showing the species were in good state of well-being since mean K values are  greater than 1.